Surgical Outcomes in Primary Benign Extradural Tumors of The Cervical Spine : A Case Report - Musfirah, Nurul; Iskandar; Ananda, Sigit (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: The prevalence of spinal tumors is rare, only about 15% of all cases of central nervous system tumors and 90% of cases occur at the age of >20 years, which is a productive age for a person. Case Report: A young 25-year-old woman came to the polyclinic complaining of weakness of both hands and feet (all limbs). The MRI results show a suspected of a space occupying lesion of the extradural spinal cord. The patient then underwent tumor removal laminectomy surgery with a posterior approach. After the operation, his motoric was improving and increased to 4/4. After three months she was able to walk and perform daily activities. Discussion: In younger patients, the tumor diagnosis may be more catastrophic, and the required treatment can have a severe impact on the patient's health-related quality of life. The patient was also very fast and assisted with early ambulation. This can be related to the progressivity of tumor cells, in this case a benign tumor with a border that is not aggressive in invading the surrounding tissue. Conclussion: Early diagnostic and complete surgical resection before the occurrence of severe symptoms will show an excellent prognosis in benign primary extradural tumor. Multidisciplinary surgical planning should therefore also include the histological grade, stage, and extent of the tumor to establish the objective biological aggressiveness of the overlying tumor and in turn estimate the feasibility of resection Keywords: Benign; Primary extradural tumor; Surgical outcome